Study model candy-making factory in Tarlac - Sales, Anthony C.; De Leon, Sonia Y. (1989.)
(NO ABSTRACT)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Food industry and trade -- Philippines -- Tarlac